Influence of reduced graphene oxide on the rheological response and chain orientation on shear deformation of high density polyethylene. (22nd March 2016) - Liu, Kangsheng; Andablo-Reyes, Efren; Patil, Nilesh; Merino, Daniel Hermida; Ronca, Sara; Rastogi, Sanjay
Abstract: The rheological response of high density polyethylene/reduced graphene oxide nanoplatelets (HDPE/rGON) composites, and the influence of rGON on chain orientation and crystallization behavior after shear flow are investigated. Melt rheology reveals the presence of strong interaction between polymer chains and the filler. Above 4.0 wt % of the filler concentration, the terminal region of frequency sweep shows changes in the linear viscoelastic properties of the composites. In particular, at these high concentrations the cross-over frequency at which the transition from predominantly elastic to viscous behavior occurs significantly shifts to lower values, indicating the formation of a solid-like percolated network. A drop in G′ at high frequency (100 rad/s) is observed in the presence of the filler, and the storage modulus shows minima at filler concentration between 2.0 and 4.0 wt %. The influence of chain–filler interaction on chain orientation, and subsequent crystallization behavior after application of shear is followed by time resolved WAXD/SAXS. The orientation of the crystalline domains was quantified by the Herman's orientation factor that supports the presence of strong chain–filler interaction. The Deborah number of reptation and retraction suggests that during the applied non-linear shear, polymer chains in the composites experience mild stretch that is not significant enough to induce crystallization at the high temperature (136 °C). However, restriction imposed by the filler on the chain mobility is pronounced enough to preserve oriented state that causes anisotropy in crystallization on cooling. The enhanced orientation with increasing filler content is conclusively attributed to the strong chain–filler interaction. Graphical abstract: Highlights: Reduced graphene oxide nanoplatelets (rGONs)/ (HDPE) nanocomposites were prepared using a two-step solution/suspension method. The rheological percolation measured by linear oscillatory rheology reveals a threshold at 4.0 wt %. Time resolved WAXD/SAXS on the HDPE/rGON samples subjected to shear flow shows strong chain–filler interaction inducing chain orientation. Combined rheological and WAXD/SAXS results demonstrate strong interaction between rGON and polyethylene chains.